Human Flourishing A Multidisciplinary Perspective on Neuroscience, Health, Organizations and Arts - Las Heras, Mireia; Grau Grau, Marc; Rofcanin, Yasin (Springer Nature, 2023)
This open access book presents a novel multidisciplinary perspective on the importance of human flourishing. The study of the good life or Eudaimonia has been a central concern at least since Aristotelian times. This responds to the common experience that we all seek happiness. Today, we are immersed in a new paradoxical boom, where the pursuit of happiness seems to permeate everything (books, media, organizations, talks), but at the same time, it is nowhere, or at least very difficult to achieve. In fact, it is not easy to even find a consensus regarding the meaning of the word happiness. Seligman (2011), one of the fathers of the positive psychology, confirmed that his original view the meaning he referred to was close to that of Aristotle. But, he recently confessed that he now detests the word happiness, since it is overused and has become almost meaningless. The aim of this open access book is to shed new light on human flourishing through the lenses of neurosciences and health, organizations, and arts. The novelty of this book is to offer a multi-disciplinary perspective on the importance of human flourishing in our lives. The book will examine further how different initiatives, policies and practices create opportunities for generating human flourishing.